Prevalence of phosphorus containing food additives in grocery stores - Janeen B. Leon; Catherine M. Sullivan; Anne M. Huml; Ashwini R. Sehgal (The Korean Society of Nephrology, 2012)
High dietary phosphorus intake is harmful for persons with kidney disease and possibly for the general public, however food labels rarely report phosphorus content. Although the quantity of phosphorus-containing food additives used within the United States food supply is not publically known, it is presumed that the consumption of these additives is substantial due to consumer reliance on processed convenience foods. We sought to determine the prevalence of phosphorus-containing food additives in commonly purchased grocery products and to compare the phosphorus content of a subset of top-selling food products with and without phosphorus additives. Study staff reviewed the labels of the 2394 most commonly purchased branded grocery products in northeast Ohio for phosphorus additives. The 5 top-selling products containing phosphorus additives from each food category were matched with similar products without phosphorus additives and analyzed for phosphorus content. Four days of sample meals were created using analyzed foods and daily phosphorus burden and pricing differential were computed. 44% of top-selling grocery items contained phosphorus additives. The additives were particularly common in prepared frozen foods (72%), dry food mixes (70%), packaged meat (65%), bread & baked goods (57%), soup (54%), and yogurt (51%) categories. Phosphorus additive foods averaged 67 mg phosphorus/100 gm more than matched non-additive containing foods (p=03). In sample meals, additive foods contributed an excess phosphorus burden of 736 mg per day. Phosphorus additive-free meals cost an average of $2.00 more per day In conclusion, phosphorus additives are commonly present in groceries and contribute significantly to the phosphorus content of foods. Moreover, phosphorus additive foods are less costly than additive-free foods. As a result, phosphorus additives may be an important contributor to hyperphosphatemia among persons with chronic kidney disease